The Manhaj of Book Al-'Ujalah fi Al-Ahadith Al-Musalsalah by Muhammad Yasin Al-Fadani: Manhaj Kitab Al-‘Ujalah fi Al-Ahadits Al-Musalsalah Karya Muhammad Yasin Al-Fadani - Zizikri, Huriaini; Rahmi, Yulia (Institut Agama Islam Negeri Kerinci, 2023)
Sheikh Muhammad Yasin al-Fadani was a great Indonesian hadith scholar in the late 20th century. A scholar of Padang, West Sumatra who was born in Makkah and is famous in various parts of the world. The scholars recognized his knowledge by dubbing him as Musnid al-Dunya. He mastered various fields of Islamic science, especially regarding the science of hadith which focused on the sanad and matan of hadith. This research discusses the book of Al-'Ujalah fi Al-Ahadith Al-Musalsalah, one of the unique and rare written works, which is used as a source of reference for science, but there has been no research that focuses on this book to find out the method and content of the book's discussion. This research uses a combined method of character study and literature study, which aims to analyze the methodology he used both in the form of systematics and characteristics of writing the book